Fleksibelitas Ibadah dan Muamalah Perspektif Fikih Pandemi - Marnita, Marnita (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2021)
The purposes of this research are; First, to analyze the flexibility of Islamic law related to Pandemic situations that contagious in every single country in the World. So, the world has new diligence in Fiqh named Pandemic Fiqh. Second, as is Pandemic Fiqh we need to review Ulama, Government Policy, and the application in public. The research method that used is qualitative research, with descriptive-analytic methods with a Literature Study approach accompanied with observations of what was happened in a community environment. The example of Pandemic Fiqh’s diligence in pure worship and not pure in an emergency like pandemic situations caused Coronavirus Disease (Covid-19) that was experienced in Indonesia at this time. Indonesia’s Ulama issuing opinions and the Government made the regulations to break the chains of spreading the Covid-19. It has been proven that created varied opinions and views in the Indonesian Muslim community. So that one side raises the understanding of the policies. On the other side, they created different conflicts of perspectives and understandings. With Pandemic Fiqh, we can unite all of the perspectives and different applications in the Indonesian Muslim community.